Hubungan Penggunaan Gadget dengan Aktualisasi Diri pada Remaja Kelas 7 di MTs Negeri 2 Banyuwangi - Nana Septiani; Badrul Munif; Fajri Andri Rahmawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
A gadget has a big influence on the teenagers’ live, where adolescents often use gadgets excessively so that they make teenagers less confident with psychological development in teenagers who do not have self-confidence, then self-actualization is very important for teenagers. This study aims to determine the relationship between gadget usage and self-actualization in 7th grade adolescents at Islamic Junior High School 2 Banyuwangi.The research used quantitative with a cross sectional research design. The samples were 165 respondents with total sampling technique. The data analysis used Chi-Square Test, SPSS 25 for windows. The instrument in this study used a questionnaire sheet on the use of gadgets and self-actualization.Most of the respondents experienced high gadget use, 94 respondents (57.0%) and most of the negative self-actualization were 88 respondents (53.3%). Statistical test results obtained p-value 0.721> = 0.005 then Ho is rejected, Ha is accepted, meaning that there is no relationship between gadget use and self-actualization in 7th grade adolescents at Islamic Junior High School 2 Banyuwangi in 2022.The high use of gadgets will affect self-actualization. There is a need for supervision and improvement of the quality of education to avoid excessive use of gadgets and optimize individual potential in order to achieve optimal self-actualization.